2015
DOI: 10.1002/jocc.12016
|View full text |Cite
|
Sign up to set email alerts
|

Wellness Among Undergraduate Students on Academic Probation: Implications for College Counselors

Abstract: This study examined levels of wellness among 403 undergraduate students on academic probation. Total wellness, 5 secondary categories of wellness, and 17 third-level categories of wellness are reported within this article. In addition, this study offers norm-group comparisons and demographic influences of wellness in regard to undergraduate students on academic probation. The results indicate that individuals on academic probation achieved higher levels of wellness in several areas of wellness than did the nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Moreover, others have suggested that students' background and demographics may influence their learning experience. For example, studies show married students are more likely to persist to graduation and have better wellness than unmarried [17]- [19]. Others have found that the educational outcomes of married students are usually better than unmarried ones.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, others have suggested that students' background and demographics may influence their learning experience. For example, studies show married students are more likely to persist to graduation and have better wellness than unmarried [17]- [19]. Others have found that the educational outcomes of married students are usually better than unmarried ones.…”
Section: Introductionmentioning
confidence: 99%